2016
DOI: 10.1159/000449259
|View full text |Cite
|
Sign up to set email alerts
|

Routine Colonoscopy after Acute Uncomplicated Diverticulitis - Challenging a Putative Indication

Abstract: Background and Aims: Most international guidelines recommend performing a routine colonoscopy after the conservative management of acute diverticulitis, mainly to rule out a colorectal malignancy; however, data to support these recommendations are scarce and conflicting. This study is aimed at determining the rate of advanced colonic neoplasia (ACN) found by colonoscopy, and hence the need for routine colonoscopy after CT-diagnosed acute diverticulitis. Methods: We retrospectively analyzed all patients hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
42
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 40 publications
(30 reference statements)
6
42
1
3
Order By: Relevance
“…From the patients scoped after the acute episode, 4 patients (2.5%) had colorectal cancer (CRC) and any of them had a previous colonoscopy. Curiously, all patients in whom CRC was diagnosed had uncomplicated disease, which is the opposite of what was found in other studies in which the risk of advanced neoplasia was higher only in those with complicated disease [4,6,7]. In our study, no immediate or late complications related to the colonoscopy were reported.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…From the patients scoped after the acute episode, 4 patients (2.5%) had colorectal cancer (CRC) and any of them had a previous colonoscopy. Curiously, all patients in whom CRC was diagnosed had uncomplicated disease, which is the opposite of what was found in other studies in which the risk of advanced neoplasia was higher only in those with complicated disease [4,6,7]. In our study, no immediate or late complications related to the colonoscopy were reported.…”
contrasting
confidence: 99%
“…In conclusion, we found a relative low prevalence of CRC in patients submitted to colonoscopy after an episode of acute diverticulitis, which is similar to what have been described by Andrade et al [4]. However, we found that the prevalence of precursor lesions such as adenomas is considerably large among patients with acute diverticulitis.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…All studies were published after 2003. There were four prospective cohort studies and 13 retrospective cohort studies ( Table ). Four studies included only patients with left‐sided acute diverticulitis, and only the subgroup of patients with left‐sided diverticulitis from one Korean study was included in the present review.…”
Section: Resultsmentioning
confidence: 99%
“…They only suggest a colonoscopy when there are potential clues on CT findings that could lead to CRC, such as an increase in intestinal wall thickness more than 6 mm, abscess, obstruction or lymph node abnormalities. When a CT-confirmed diverticlutis is in the absence of other concering or intermediate findings, there is no benefit in a follow-up colonoscopy [23][24][25][26]. Recently, 3 meta-analyses were published concerning the risk of CRC after a radiologic confirmed diagnosis of acute diverticulitis.…”
Section: Discussionmentioning
confidence: 99%